Training for Improving Energy Efficiency Awareness in The Home Industry Sector - Saputri, Fahmy Rinanda; Andarini, Rahmi (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service aims to promote energy efficiency awareness for the home industry sector, so that energy efficiency becomes a culture both in household domestic activities and in the production process. The method of implementing this service uses training with the participants of this activity are the residents around Keranggan Ecotourism Village who run businesses and have household industries. The evaluation instrument uses in this community service is the increase of awareness level of the participants regarding energy efficiency behaviour, such as selecting energy efficient equipment, recording the electricity consumption, and setting the operational hour of energy-using equipments such as lamps, rice cookers, and so on. The results of this service show that participants gained knowledge in recording electricity consumption and knowing the activities that have an impact on increasing electricity consumption and develop plans for energy efficiency programs.